Netrin1 produced by neural progenitors, not floor plate cells, is required for axon guidance in the spinal cord - Varadarajan, Supraja G. (Neuron, 2017)
Netrin1 has been proposed to act from the floor plate (FP) as a long-range diffusible chemoattractant for commissural axons in the embryonic spinal cord. However, netrin1 mRNA and protein are also present in neural progenitors within the ventricular zone (VZ), raising the question of which source of netrin1 promotes ventrally-directed axon growth. Here, we use genetic approaches in mice to selectively remove netrin from different regions of the spinal cord. Our analyses show that the FP is not the source of netrin1 directing axons to the ventral midline while local VZ-supplied netrin1 is required for this step. Furthermore, rather than being present in a gradient, netrin1 protein accumulates on the pial surface adjacent to the path of commissural axon extension. Thus, netrin1 does not act as a long-range secreted chemoattractant for commissural spinal axons, but instead promotes ventrally-directed axon outgrowth by haptotaxis, i.e. directed growth along an adhesive surface.